Custo-efetividade de intervenções no aumento da adesão a terapia antirretroviral e redução da carga viral em pacientes com HIV - Santos, Wendel Mombaque dos (2019)
This study presents an economic cost-effectiveness study of non-pharmacological interventions to increase adherence to antiretroviral treatment and reduction of circulating viral load in people living with HIV (Human Immunodeficiency Virus). The purpose of this study is to evaluate which interventions are cost-effective, since different interventions may have different cost-effectiveness values. The research starts from the reality of the HIV epidemic, taking into account the context of Public Health in Brazil since a constant in the incidence of HIV has been observed and one of the factors that contribute to the reduction of the risk of infection is high values of adherence to HIV. Antiretroviral treatment and low viral load. A cost-effectiveness study was carried out to collect data from the University Hospital of Santa Maria and systematic reviews of the literature. The economic model was performed through the decision tree, and its sensitivity was evaluated through the Monte Carlo analysis. The results demonstrated that the use of text messages had been shown to be the most cost-effective intervention both for increasing adherence to antiretroviral treatment and for reducing circulating viral load in people living with HIV. It is concluded that the use of non-pharmacological interventions, in this case, the sending of text messages, bring clinical and economic benefits to the context of public health in Brazil. In the clinical context, increased adherence to antiretroviral treatment and reduction of viral load were observed, resulting in reductions in complications related to HIV infection and reduction of the risk of new infections. The economic benefit is related to the lower cost of treatment of complications due to non-adherence and high viral load, as well as future expenses in the treatment of new infections. In this way, the use of interventions based on text messaging is cost-effective and should be used as a tool for health promotion in the context of public health.